STRATEGY AND TACTICS OF FINANCIAL POLICY OF KAZAKHSTAN IN THE CONDITIONS OF DEVELOPMENT OF INTEGRATION PROCESSES - Sembiyeva L. M.; Оrozonova А. А.; Zhagyparova A. O.; Tulegenova Zh. U. (Scientific Journal of Pedagogy and Economics, 2019)
This article discusses the strategy and tactics of the financial policy of Kazakhstan in the context of integration processes. In the process of creating a single financial market of the EAEU, subject to enhanced integration of the Union countries, great attention is paid to effective financial policy, since its effectiveness depends on completing the process of harmonization of state legislations in the financial sector, as well as ensuring the effective development of national economies of the participants of this integration association.